Quality of Life in Children with Obsessive-Compulsive Disorder - Vieira, Joana (2016)
Introduction: Obsessive-compulsive disorder is a psychiatric disorder stated as one of the most debilitating diseases in the developedworld. However, not much is known about how this disease impairs patients’ quality of life in children.Material and Methods: We conducted a research in PubMed and Thomson Reuters Web Of Science using the following terms: ‘Quality of life’, ‘Obsessive-compulsive disorder’, ‘Child’, ‘Pediatrics’ and ‘Adolescent’. Of the 138 papers retrieved with this search, five articles corresponded to the aim of this review. We analyzed quality of life in children with obsessive-compulsive disorder comparing with general population and searching the relation with other clinical variables such as sex, age, comorbidities, symptoms dimension, symptoms severity, family accommodation and quality of life.Results: Albeit studies results not being concordant regarding the different dimensions analyzed, our findings pointed to an overall decrease of quality of life in children with obsessive-compulsive disorder. The presence of co-morbidities, symptoms severity and obsessions with harm/aggression content are the variables that have a higher influence in quality of life levels.Discussion: The small number of articles found and the fact that their methodology was extremely heterogeneous made it difficult to state robust conclusions. Despite that, our findings agree with other studies in adults.Conclusion: Quality of life in children and adolescents with obsessive-compulsive disorder must be better explored in future researches. We suggest the introduction of quality of life as a routinely used instrument in patient’s assessment and in treatment response evaluation.